Identification of Microflora in Butter Samples from Turkey by Using the Microbial Identification System - OZTURK YILMAZ, S. (Asian Journal of Chemistry, 2010)
A total 138 bacterial strains and 52 fungi isolates were isolated from 53 butter samples collected from grocery stores in Erzurum, Turkey in the winter season of 2000. They were identified based on fatty acid methyl esters (FAMEs) analysis with microbial identification system (MIS; MIDI Inc., Newark, Del.). All of the isolates and 4 reference bacterial strains were identified at species level. The most abundant bacterial species found was Enterococcus faecalis followed by Staphylococcus hominis, Micrococcus luteus, Pseudomonas putida, P. fluorescens, Brevibacillus brevis, Streptococcus sanguis, Weissella viridescence, Lactococcus lactis-lactis and Lactobacillus kefir. However, only 73 % (38) of the fungi isolates tested could be identified with MIS at the genus or species level. The most prevalent fungi species was found to be Aspergillus versicolor followed by A. flavus, Rhizophus spp., Penicillium spp., Fusarium spp., Exophiala salmonis, Torulomyces rubrum, Phoma spp., Ulocladium spp., Geotricum candidum and Paecilomyces variotii. The remaining 14 fungi isolates could not be identified with MIS. Present MIS results are confirmed with conventional methods used for identification of the reference and randomly selected microorganisms isolated in this study. Present results suggest that MIS system is a rapid and reliable method for identification of microflora of butter samples.